2020
DOI: 10.1155/2020/3968625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lane Policies on Freeway Traffic Mixed with Manual and Connected and Autonomous Vehicles

Abstract: Connected and autonomous vehicles (CAVs) have become the highlights of traffic. Researchers in this field have proposed various traffic management measures to enhance the capacity and efficiency of traffic with CAVs, especially mixed traffic of CAVs and manual vehicles (MVs). Exclusive lane setting is included. However, exclusive lane policy-related researches for mixed traffic of CAVs and MVs were very limited, and the influence of number and location of exclusive lanes on the mixed traffic was unclear. To fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In recent years, intelligence agents with connection characteristics have attracted much attention, especially in the field of connected and automated vehicles (CAVs). CAVs can take rational dynamics automatically by perceiving information with intervehicle communications [1,2], including vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communication. However, fully mature CAVs, which meet Level 5 in the Society of Automotive Engineers (SAE) J3016, are not available because of the current limitations on communication technologies [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, intelligence agents with connection characteristics have attracted much attention, especially in the field of connected and automated vehicles (CAVs). CAVs can take rational dynamics automatically by perceiving information with intervehicle communications [1,2], including vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communication. However, fully mature CAVs, which meet Level 5 in the Society of Automotive Engineers (SAE) J3016, are not available because of the current limitations on communication technologies [3].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [44] studied the influence of CAV dedicated lanes on the freeway heterogeneous traffic flow from the perspective of traffic safety. Hua et al [45] studied the influence of different dedicated lane strategies on the heterogeneous traffic flow. e results showed that the CAV dedicated lanes could improve the freeway capacity, but dedicated lanes for MVs had little impact on the improvement of the freeway capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the development of 5G technology for mobile communication and intelligent technology, intelligent vehicles are rapidly developing. Soon, a mixture of various types of intelligent vehicles will become normal [9], and manual driving vehicles (MVs), connected manual vehicles [10,11] (CMVs), automated vehicles [12,13] (AVs), and connected automated vehicles [14][15][16] (CAVs) will simultaneously share the road [17][18][19]; moreover, the driving environment will become complex and changeable, and there will be an increasing number of factors that could induce cognitive distracted driving behaviour. Cognitive distraction will seriously affect driving safety [20], so such distraction in a connected environment is an important research topic addressed in this paper.…”
Section: Introductionmentioning
confidence: 99%